Effectiveness of the UPT Puskesmas Rappang Lung Botting Program as an Effort to Prevent Stunting - Magfirah, Elsya; Mardhatillah, Mardhatillah; Adri, Khaeriyah; Sulaiman, Zulkarnain (Jurnal Administrasi Politik dan Sosial, 2024)
Stunting Stunting is a malnutrition that results in impaired growth and development of the child. As a form of stunting prevention efforts, UPT Puskesmas Rappang introduced the Pulmonary Botting program. This study aims to determine the effectiveness of such programs. The study used a quantitative approach with a Cross-Sectional study design. Data were collected through questionnaires/questionnaires and analyzed using the Chi-Square test to determine the relationship between each indicator and stunting prevention efforts. The results of the analysis showed that the effectiveness of the program goal indicator with P-Value 0.016 0.05 and Program Monitoring with P-Value 0.108 0.05 meaning there was no significant relationship. These findings suggest that the effectiveness of the Lung Botting program in stunting prevention is strongly influenced by the successful socialization of the program and the clarity of the program goals set. This study is expected to provide benefits in improving program effectiveness, in particular by focusing on strengthening program monitoring indicators and target accuracy, so that programs can be more targeted and better supervised to achieve optimal results in stunting prevention.